Cardiovascular and Vector-Cardiographic Effects of Articaine Anesthesia with Epinephrine - Christoph Pökel; Antina Schulze; Martin Busse (International Journal of Dentistry)
The aim was to investigate the vector-cardiographic effects in patients submitted to dental extraction under local anesthesia. Twenty-one patients aged 36.6 ± 12.4 years with a clinical and radiographic indication of mandibular or maxillary tooth extraction were enrolled. The intervention was a local or mandibular nerve block anesthesia with 4% articaine hydrochloride containing epinephrine (1 : 100,000; 40 mg/ml + 10 μg/ml). Blood pressure (BP), heart rate (HR), pulse wave transit time, and vector-cardiography data were recorded throughout 3 min before and 5 min after injection. QRS- and T-wave area under the curve (QRSAUC/TAUC) were calculated from the X/Y/Z QRS-vector or T-vector. T-wave amplitude (TAM), TAUC values, and diastolic BP decreased, and HR significantly increased 4 min after injection. A transient moderate HR drop and a corresponding small increase in TAM and TAUC immediately after the injection procedure may be explained by a decreased sympathetic tone due to psychological relief. In dental anesthesia, the systemic epinephrine effects are represented by a decrease in TAUC. These effects are most pronounced in the X- and Y-leads. The 3D determination of vector planes or amplitudes is a simple method to register the sympathetic tone in local anesthesia independently of possible effects on T-wave characteristics in single leads. In conclusion, T-wave determination may help to detect even small increases in systemic adrenaline concentration in case of accidental intravascular injection. At the same time, full rhythm and spatial ischemia control is provided.